Into Space A Journey of How Humans Adapt and Live in Microgravity - Russomano, Thais; Rehnberg, Lucas (IntechOpen, 2018)
Our anatomy and physiology have been completely shaped by Earth's gravity. All body systems function in synergy with this unseen force. Yet, as we journey further and longer into space, our bodies must conform to a new reality, wherein gravity is absent or reduced, cosmic radiation threatens and our social and familial connections become distant. Into Space: A Journey of How Humans Adapt and Live in Microgravity gives an overview of some of the physiological, anatomical and cellular changes that occur in space and their effects on different body systems, such as the cardiovascular and musculoskeletal, and touches on cultural and psychosocial aspects of leaving behind family and the safety of Earth. It further addresses the complexity of manned space flights, showing how interdisciplinary this subject is and discussing the challenges that space physiologists, physicians and scientists must face as humans seek to conquer the final frontier.